2001
DOI: 10.1161/hc4001.098048
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Induces Circadian Gene Expression of Clock Genes in Cultured Vascular Smooth Muscle Cells

Abstract: Background-Daily rhythms of mammalian physiology and endocrinology are regulated by circadian pacemakers. The master circadian pacemaker resides in the suprachiasmatic nucleus, which is located in the hypothalamus of the brain, but circadian oscillators also exist in peripheral tissues. Because many studies have demonstrated apparent circadian variations in the frequency of cardiovascular disorders, it is of great interest to investigate a possible relation between circadian gene expression and cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 16 publications
4
118
1
1
Order By: Relevance
“…First, CRP acts on vascular smooth muscle cells by upregulating the angiotensin type I receptor (23) and stimulating the migration and proliferation of smooth muscle cells, in addition to the production of reactive oxygen species. Inhibition of rennin-angiotensin system (RAS) by angiotensin receptor blocker (ARB) or ACE inhibitor (ACEI) resulted in a reduction of vascular smooth muscle cell proliferation (24,25), and improved the BaPWV which is a parameter of atherosclerosis (26). In addition, angiotensin II, via the type-1 (AT1) receptor, stimulates NADPH oxidase and enhances production of reactive oxygen species (ROS) (27), which in turn contributes to endothelial dysfunction by inactivating nitric oxide (NO) (28).…”
Section: Discussionmentioning
confidence: 99%
“…First, CRP acts on vascular smooth muscle cells by upregulating the angiotensin type I receptor (23) and stimulating the migration and proliferation of smooth muscle cells, in addition to the production of reactive oxygen species. Inhibition of rennin-angiotensin system (RAS) by angiotensin receptor blocker (ARB) or ACE inhibitor (ACEI) resulted in a reduction of vascular smooth muscle cell proliferation (24,25), and improved the BaPWV which is a parameter of atherosclerosis (26). In addition, angiotensin II, via the type-1 (AT1) receptor, stimulates NADPH oxidase and enhances production of reactive oxygen species (ROS) (27), which in turn contributes to endothelial dysfunction by inactivating nitric oxide (NO) (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that, in addition to circulating factors, the tissue renin-angiotensin-aldosterone secretion of the cardiovascular system exhibits diurnal variation (41), possibly in relation to a clock gene (42,43). In addition to the reduction of the morning BP level, the morning activation of the tissue renin-angiotensin-aldosterone system might be effectively suppressed by bedtime administration of an ACE inhibitor, leading to more effective protection against hypertensive target organ damage and cardiovascular events in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the master clock is located in the suprachiasmatic nuclei, but most peripheral tissues contain circadian clocks. 1 These transcriptional modulators have been identified within the heart (cardiomyocytes, vascular smooth muscle cells, endothelial cells, and fibroblasts) [2][3][4][5] and have been shown to regulate apoptosis, contractile function, metabolism, and gene expression and therefore confer the selective advantage of anticipation, permitting the cell to respond appropriately to a stimulus at a given time of the day. 6 Recently, experimental studies have shown that cardiomyocyte circadian clock affects the response of the heart to various stresses including ischemia/reperfusion by modulating multiple cardioprotective signaling pathways.…”
Section: Introductionmentioning
confidence: 99%